BALALAR DRAMATURGIYASÍNÍŃ RAWAJLANÍWÍNDA JAS TAMASHAGÓYLER TEATRÍNÍŃ TUTQAN ORNÍ - Ataniyazova, G.S. (SCIENCE and SOCIETY, 2023)
In the article was analyzed scientifically the history and establishment of the Theater of Young Audiences and the direction of its development until today.